The Quest for Sustainable Development in the Context of Insecurity: Some Critical Reflections (The Strategic Review for Southern Africa, 2020)
This paper considers the possibility of realizing “peaceful and inclusive societies for sustainable development; providing access to justice for all and building effective, accountable and inclusive institutions at all levels specifically in Africa”. This is goal 16 of the United Nations Sustainable Development Goals (SDGs). As configured, peace, security and development are treated as integral subsets of sustainable development. The paper contends that this goal holds the key to the realization of other SDGs in the African context. In examining the achievability of this goal, the concept and essence of development in general and sustainabledevelopment in particular were examined. The paper argues that the well-being of a state and its people is the primary essence of development. Furthermore, development is considered as connoting a state’s capacity to provide enabling conditions such as peace and freedom that sustain general well-being. Development is also a characteristic of a state-system which cannot sustain itself in the absence of peace, security and democracy. The approach and method followed in the paper are largely qualitative and analytical. Data from documentary analysis were relied upon to develop a conceptual framework of peace, security, democracy and development. Findings show that the evolvement of sustainable development remains difficult in Africa because Africa’s development trajectory remains largely disconnected and disjointed. For Africa to achieve sustainable development goals (SDGs), serious peace and security challenges must be effectively addressed. Broad suggestions to ensure that well-articulated development paradigm in which peace, security, democracy and policy stability are strategically positioned, linked and integrated to the degree that they provide mutual support and reinforcement to one another are made.